Ludwig Feuerbach’s conception of the religious alienation of man and Mikhail Bakunin’s philosophy of negation - Uglik, Jacek (Studies in East European thought, 2010)
In this paper we attempt to prove that it was Ludwig Feuerbach’s anthropology that influenced Bakunin’s philosophical path. Following his example Bakunin turned against religion which manipulates, as Hegelianism does, the only priority human being has—another human being. Although Feuerbach’s philosophy did not involve social problems present at Bakunin’s works, we would like to show that it was Feuerbach himself who laid foundation for them and that Bakunin’s criticism of the state was the natural consequence of Feuerbach’s struggle for the individual. Mikhail Alexandrovich Bakunin proved that Feuerbach’s attempts to rise anthropology to the rank of theology are not sufficient to free the individual from the power of abstractions as in his opinion it is not only God (religion) that should be overthrown but also the state.